2019
DOI: 10.1097/med.0000000000000468
|View full text |Cite
|
Sign up to set email alerts
|

Triglycerides and triglyceride-rich lipoproteins in the development and progression of atherosclerosis

Abstract: Purpose of reviewIn this review, we intend to show the heterogenicity of the triglyceride group, including the triglyceride-rich lipoproteins and its subparticles, apolipoproteins, and its role in atherogenesis through epidemiological and genetic studies, observing the association of these various components and subclasses with subclinical atherosclerosis and cardiovascular events. Also, we reevaluated the moment of blood collection for the triglyceride measurement and its repercussion in atherosclerosis. Fina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 85 publications
0
24
0
2
Order By: Relevance
“…TGs are a causal risk factor for atherosclerotic cardiovascular diseases, and many mechanisms involving both atherogenesis and thrombogenesis have been proposed. The specific markers of TG metabolism, such as lipoprotein lipase and apolipoprotein C‐III, are entrapped in the subendothelial space and scavenged by resident macrophages, contributing to macrophage foam cell formation and plaque formation and progression 12 . Moreover, the lipolytic products of TGs also activate numerous proinflammatory, procoagulant, and proapoptotic signaling pathways that play fundamental roles in the pathogenesis of atherosclerosis 13 .…”
Section: Discussionmentioning
confidence: 99%
“…TGs are a causal risk factor for atherosclerotic cardiovascular diseases, and many mechanisms involving both atherogenesis and thrombogenesis have been proposed. The specific markers of TG metabolism, such as lipoprotein lipase and apolipoprotein C‐III, are entrapped in the subendothelial space and scavenged by resident macrophages, contributing to macrophage foam cell formation and plaque formation and progression 12 . Moreover, the lipolytic products of TGs also activate numerous proinflammatory, procoagulant, and proapoptotic signaling pathways that play fundamental roles in the pathogenesis of atherosclerosis 13 .…”
Section: Discussionmentioning
confidence: 99%
“…31 TGRL particles are regulated by apolipoprotein C-III (apoC-III) 2830 and their atherogenic fractions (such as IDL, VLDL remnants and chylomicron remnants) have been shown to migrate across the endothelial wall where they are engulfed by macrophages, forming foam cells, inducing low-grade inflammation and instigating atheromatous plaque growth. 32 Numerous genetic and clinical studies have shown that RC levels, or their highly correlated triglyceride levels, are predictive of ASCVD and all-cause mortality. 1012,3335 A Mendelian randomization study of 60,000 participants demonstrated that a 39 mg/dL (1 mmol/L) greater level of non-fasting RC was associated with a three-fold increase in CRP levels and higher rates of ischemic heart disease.…”
Section: Discussionmentioning
confidence: 99%
“…These lipoproteins are novel biomarkers driving residual cardiovascular risk in our contemporary era of elevated incidence rates of obesity, diabetes, and metabolic syndrome [15]. In particular, VLDL remnants (as well as LDL particles) have been shown to migrate across the endothelium where they are entrapped by macrophages, forming foam cells, promoting low-grade inflammation and facilitating atheromatous plaque growth [16]. There is a need to better define the relationship between plasma lipoprotein particles that carry triglycerides and cholesterol (especially VLDLs, IDLs, and their remnants), Lpa and the relative atherogenicity of those lipoproteins versus LDL.…”
Section: Discussionmentioning
confidence: 99%